Comparison between two FISH techniques in the in vitro study of cytogenetic markers for low-dose X-ray exposure in human primary fibroblasts - Nieri, Dino; Berardinelli, Francesco; Antoccia, Antonio; Tanzarella, Caterina; Sgura, Antonella (Frontiers in Genetics, 2013)
This work is about the setup of an in vitro system to report low-dose of X-rays as measured as cytogenetic damage. Q- and m-FISH, for telomere length and chromosome instability analysis respectively, were compared to evaluate their sensitivity in the low-dose range in human primary fibroblasts. No telomere length modulation was observed up to 1 Gy in cycling fibroblasts, though reported for high doses, by that frustrating the purpose of using it as a low-exposure marker. To date the m-FISH is the best setup for the assessment of the chromosome structural damage: it allows stable and instable aberrations to be detected all over the karyotype. Stable ones such as balanced translocations, are not eliminated due to cell-cycle as unstable ones, so they are considered transmissible markers for retrospective dosimetry. The induction of chromosome damage showed a clear dependence on dose delivered; unstable aberrations were demonstrated after doses of 0.1 Gy, and stable aberrations after doses higher than 0.5 Gy. Summarizing, q-FISH is unfit to report low exposures while m-FISH provides better results: unstable aberrations are sensible short-term reporters, while stable ones long report exposures but with a higher induction threshold.